The Design of Library Data Warehouse Using OLTP Result of Services Analysis - Ariawan, Pasek Agus; Ardiada, Made Dwi; Sudarmojo, Yanu Prapto (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
The library is the primary means used in development efforts as well as an increase in knowledge. Library holds a very large role in the spread of information because the library provides collections that can be used as a reference for the Civitas academic. Data Warehouse is a system that takes and consolidate data periodically from a source system into a dimensional or normalization of the data store. The purpose of this research was to analyze the information about the business process and create the initial means for taking quick decisions in related service quality evaluation in libraries and Understand the trends/interests and make forecasts better decisions in the evaluation of the quality of related services in the library.